Geologi Wilayah Desa Boidu, Kecamatan Bulango Utara, Kabupaten Bone Bolango - Tumelap, Irka Priwanda; Permana, Aang Panji; Kasim, Muh (Journal of Applied Geoscience and Engineering, 2025)
Regionally, intrusive rocks are quite widespread in the study area, belonging to the Diorite Bone (Tmb) formation. The formation is composed of Diorite, Quartz Diorite, Granodiorite and Adamellite. This study aims to determine the condition of lithology, geological structure and geomorphology. The method used in this research is expolrative, namely obtaining data directly from the field and then analyzing petrology and petrography laboratories. The geomorphology of the study area is divided into 2 geomorphological units, namely; intrusion hills and alluvial plain units. The study area is unofficially divided into three rock units when sorted from oldest to youngest, namely: Diorite rock unit, Granodiorite unit (Middle-Late Miocene), and alluvial sediment unit (Holocene). The geological structure of the study area consists of tensile bridging with a southwest - northeast direction.